Experimental measurements and modelling of vapour-liquid equilibrium of 2, 3, 3, 3-tetrafluoropropene (R-1234yf) + 1, 1, 1, 2, 2-pentafluoropropane (R-245cb) system. (November 2019) - Valtz, Alain; Abbadi, Jamal El; Coquelet, Christophe; Houriez, Céline
Highlights: VLE data for the R-245cb + R1234yf mixture were experimentally measured. The experimental data were correlated with the NEoS and Peng–Robinson EoS, with the classical mixing rules. Comparison with literature data values is realized. Abstract: Isothermal vapour-liquid equilibrium (VLE) of the R-1234yf+R-245cb binary system were measured using a "static-analytic" apparatus at temperatures from 283.39 to 343.27 K. The data measured were compared with literature data for conformity checking. Albeit both VLE measurement sets are in good accordance, an unexpected behaviour was observed for the relative volatility calculated on the basis of the literature data. The thermodynamic model used for the calculations reproduces very well R-1234yf+R-245cb VLE data, and is based on a 3-parameter cubic equation of state (denoted by NEoS). This cubic equation of state was associated with the Mathias–Copeman alpha function and van der Waals mixing rules. Comparisons were also done with Peng–Robinson EoS with similar alpha function and mixing rules.